Hubungan Pendampingan Suami, Kecemasan dan Senam Hamil Terhadap Lama Persalinan Kala Ii di PMB K. Cikancana Kab. Cianjur Tahun 2023 - Ai Diani; Astarie, Aida Diana; Madinah (Indonesian Journal Publisher, 2023)
Long labor is one of the problems in labor that can endanger the safety of the mother and fetus. The absence of the husband during childbirth, maternal anxiety and never doing physical activity such as during pregnancy can increase the risk of prolonged labor, especially during time II. The purpose of this study is to determine the relationship between husband assistance, anxiety and pregnancy exercise on the duration of the second stage of labor in PMB K Cikancana, Cianjur Regency in 2023. Methods This study used a type of analytical descriptive research using quantitative methods, with cross-sectional methods. The sampling technique used in this study uses non-probability sampling techniques with population sampling The total sample in this study includes maternity mothers at PMB K Cikancana, Cianjur Regency in 2023, in August a total of 30 respondents. The results of the Chi-Square test in this study showed that there was a significant relationship between husband assistance and the length of labor in time II, obtained a P.Value value of 0.001 (< 0.05), anxiety with the length of labor in time II, obtained a P.Value value of 0.011 (< 0.05), pregnancy exercise with a length of labor when II, obtained a P.Value value of 0.006 (< 0.05). The conclusion of this study is that there is a relationship between husband assistance, anxiety and pregnancy exercises